Blended & flipped learning case studies in Malaysian HEIs - Mohamed Amin Embi (Pusat Pengajaran & Teknologi Pembelajaran, Universiti Kebangsaan Malaysia, 2014)
The purpose of the book is to provide an overview of the implementation of blended learning and flipped learning in selected Malaysian higher education institutions. The book is divided into 2 sections: Section A discusses Blended Learning; while section B elaborates on Flipped Learning.